Management of Islamic Education Institutions in Motivation and Decision Making - Candra Wijaya; Poniman Adyanto; Darno Darno; Yulinar Yulinar; Muhammad Fadli (STAI Hubbulwathan Duri, 2022)
The study aims to describe the role of school principals in making decisions to improve the quality of education at MTs Islamiyah YPI Batang Kuis. It reveals 1) The decision-making process carried out by school principals to improve the quality of education, 2) Participation in decision-making carried out by school principals to improve education quality, and 3) Evaluation of the implementation of decisions to improve the quality of education. The method used is qualitative, while the approach used is descriptive, with research data collection obtained by observation, Interview, and documentation techniques. The results of this study reveal the findings, namely: 1) The decision-making process carried out by the Principal of MTs Islamiyah YPI Batang Kuis by analyzing the problem, developing alternative solutions, deciding on alternatives, implementing and evaluating 2) Participation carried out by the principal of MTs Islamiyah YPI Batang Kuis is to involve: foundations, teachers' councils and administrative staff in decision making. To carry out this participation can be done in various ways, for example by meeting / deliberation and asking for responses, 3) Evaluation of the implementation of decisions made by the principal of MTs Islamiyah YPI Batang Kuis carried out by all components within the institution and who are responsible for evaluating decisions, namely all parties involved in implementing the decision.